(untitled) (Submission and Review of Research -Biological Sciences Series, 2025)
The study was conducted in the laboratories of the Faculty of Agriculture and the laboratories of the Higher Institute of Marine Research at Tishreen University in 2022-2023. The study aimed to determine the chemical composition and sensory and biological properties of the natural sweetener Stevioside extracted from the dry leaves of stevia grown in Lattakia by two methods and compare them with each other. The importance of the research comes as it studies the characteristics and properties of a natural sweetener that is a good alternative to artificial sweeteners in terms of nutrition and health. Stevioside was extracted from the dry leaves of Stevia by two methods: The first is aqueous extraction was performed according to (Woelwer, (2010, and the second is alcoholic extraction was performed according to (Nikolai, (2001. The analysis of stevia leaves (moisture, ash, protein, fat, crude fiber, total carbohydrates) was performed according to (AOAC,1989), the degree of sweetness was estimated according to (Isima and Kakayama,1976) and the content of Stevioside was estimated by HPLC according to Nishiyama,1992), where the content of stevia leaves of moisture, ash, protein, and fat came respectively (6.2%, 8.3%, 11.2%, 4.1%) while the carbohydrate content was high (59.4%), and the highest amount of Stevioside was obtained by alcoholic extraction (12.7%) compared to aqueous extraction (8.2%). The results also showed that there was some bitter taste in Stevia leaves compared to sucrose, and the relative sweetness of the aqueous extracted stevia solution was 110 times that of sucrose, while it was 150 times that of sucrose in the alcoholic extract.